Manipulasie van sori op blare van die seweweeksvaring (Rumohra Adiantiformis [G. Forst.] Ching) (Afrikaans) - Wessels, A.B. (University of Pretoria, 2013)
Dissertation (MSc(Agric))--University of Pretoria, 2011.